2016
DOI: 10.1073/pnas.1613007114
|View full text |Cite
|
Sign up to set email alerts
|

Cell morphology drives spatial patterning in microbial communities

Abstract: The clearest phenotypic characteristic of microbial cells is their shape, but we do not understand how cell shape affects the dense communities, known as biofilms, where many microbes live. Here, we use individual-based modeling to systematically vary cell shape and study its impact in simulated communities. We compete cells with different cell morphologies under a range of conditions and ask how shape affects the patterning and evolutionary fitness of cells within a community. Our models predict that cell sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(157 citation statements)
references
References 57 publications
8
146
3
Order By: Relevance
“…We now explore the global implications of allowing rest length extension rate to vary with spring compression in our model. This study is motivated by experimental evidence supporting the thesis that mechanical forces shape the dynamics of collectives [1214, 27, 31, 35]. In particular, it has been shown that mechanical forces can become sufficiently large to slow cell growth [10].…”
Section: Two-dimensional Microfluidic Trap Geometries: Results Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We now explore the global implications of allowing rest length extension rate to vary with spring compression in our model. This study is motivated by experimental evidence supporting the thesis that mechanical forces shape the dynamics of collectives [1214, 27, 31, 35]. In particular, it has been shown that mechanical forces can become sufficiently large to slow cell growth [10].…”
Section: Two-dimensional Microfluidic Trap Geometries: Results Andmentioning
confidence: 99%
“…Forces acting on the constituent cells play a critical role in the complex dynamics of cellular growth and emergent collective behavior [5, 9, 11, 12, 2931, 33], and biological evolution [13]. Agent-based models, therefore, need to be able to model the force exerted by growing cells, as well as the mechanical interactions induced by cell-cell contacts or contact with environmental boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…3a; t = − 26, P = 3 × 10 −136 ). Particle shape has been shown to affect numerous systems from randomly packed colloids to biofilms 21,22 ; here we examine the role of cellular aspect ratio on packing within the fractal pole-budding geometry of snowflake yeast. As previous exhaustive experiments 7 have validated that the fractal-like snowflake yeast growth form holds for week-1 and week-8 clusters of any size, the role of cell shape becomes a question of geometry.…”
Section: Lettersmentioning
confidence: 99%
“…The curved shape of Caulobacter crescentus, for example, promotes the formation of biofilms as hydrodynamic forces reorient single cells to optimize 245 daughter cell attachment (58); this process also nucleates clonal clusters under strong flow (59,60). Simulations and experiments with engineered variants of E. coli suggest that rod-shaped bacteria can obtain a competitive advantage over spherical cells in colonies on agar plates, because rod-shaped cells burrow underneath spherical cells and spread more effectively to access fresh nutrients on the colony periphery (61). Filamentation has been observed in a wide variety of bacteria and eukaryotic microbes; this morphology is implicated in assisting spatial 250 spread through soil or host tissue, and defense against phagocytosing ameboid predators (56, 62, 63).…”
Section: Discussionmentioning
confidence: 99%